African water network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Kenyan network KWAHO and the Environment Liaison Centre (ELC), also based in Nairobi, are joining to create a new network of African NGOs which will increase their involvement in projects concerned with the provision of water. KWAHO PO Box...